A case of epidemic myalgia with symptoms resembling acute purulent spondylitis and discitis. Issue 1 (December 2016) - Kenzaka, Tsuneaki; Hida, Yukariko; Matsumoto, Masanori; Akita, Hozuka
Abstract Background Epidemic myalgia is a disease that presents with fever and extreme myalgia of the trunk due to an acute enterovirus infection. The trunk pain is mainly in the chest or in the epigastrium. We aimed to highlight a case of epidemic myalgia where initial diagnosis needed differentiation from acute purulent spondylitis and discitis. Case presentation A 33-year-old woman presented with fever, chills, and acute episodes of low back pain. The sole unusual finding was pain upon spinal percussion, limited to the 4th and 5th lumbar vertebrae. Spinal MRI showed no abnormality. Paired serum samples from disease days 4 and 15 showed a significant increase in coxsackievirus B3–neutralizing antibodies. Based on this course, we diagnosed epidemic myalgia. Conclusions Epidemic myalgia should be considered when differentiating acute low back pain accompanied by fever.